Charge‐Transfer Salts of 6, 6‐Dicyanopentafulvenes: From Topology to Charge Separation in Solution. Issue 51 (10th August 2018) - Finke, Aaron D.; Zalibera, Michal; Confortin, Daria; Kelterer, Anne‐Marie; Mensing, Christian; Haberland, Sophie; Diederich, François; Gescheidt, Georg
Abstract: 6, 6‐Dicyanopentafulvene derivatives and metallocenes with redox potentials appropriate for forming their radical anions form highly persistent donor–acceptor salts. The charge‐transfer salts of 2, 3, 4, 5‐tetraphenyl‐6, 6‐dicyanofulvene with cobaltocene (1⋅ Cp2 Co) and 2, 3, 4, 5‐tetrakis(triisopropylsilyl)‐6, 6‐dicyanofulvene with decamethylferrocene (2⋅ Fc*) have been prepared. The X‐ray structures of the two salts, formed as black plates, were obtained and are discussed herein. Compared with neutral dicyanopentafulvenes, the chromophores in the metallocene salts show substantial changes in bond lengths and torsional angles in the solid state. EPR, NMR, and optical spectroscopy, as well as superconducting quantum interference device (SQUID) measurements, reveal that charge‐separation in the crystalline states and in frozen and fluid solutions depends on subtle differences of redox potentials, geometry, and on ion pairing. Whereas 1⋅ Cp2 Co reveals paramagnetic character in the crystalline state and in solution, compound 2⋅ Fc* shows a delicate balance between para‐ and diamagnetism, depending on the temperature and solvent characteristics. Abstract : Take it or leave it : 6, 6‐Dicyanopentafulvenes are readily reduced by metallocene derivatives to give charge‐transfer salts with unusual properties (see figure). The effect of structure and topology on the ion‐pairing and magnetic properties of these charge‐transfer salts, both in solution and in the solid state, are discussed.